Public expenditure and growth dynamics in Indian agriculture: Trends, structural breaks, and linkages - Akber, Nusrat; Kumar, Anjani; Bathla, Seema (International Food Policy Research Institute, 2023)
The present study analyzes temporal and spatial trends in public expenditure on agriculture and irrigation in India. It links sub-period growth performance with expenditure based on structural breaks. The analysis pertains to the period between 1992/1993 and 2019/2020. This is a period that has witnessed a stagnation, and even a decrease in public expenditure in the agricultural sector and a resulting deceleration in productivity growth, which was then followed by a revival in both expenditure and output. Significantly expenditure on subsidies of key inputs, viz. fertilizer, irrigation, and power, however, has not incentivized farmers to increase output and productivity to achieve a higher rate of growth. Empirical findings based on the first-difference regression analysis confirm that agricultural growth is determined by public expenditure on agriculture and irrigation; across the states, however, input subsidies alone are shown to be less, or not at all, efficient. Funds to agriculture and irrigation should be increased in proportion to their contribution to the state domestic product, and input subsidies should be rationalized by weighing their positive welfare effects against their cost to the exchequer.